The experience of couples in intimate relationships when the woman is a survivor of child sexual abuse: A phenomenological study. - Champion de Crespigny, Janet Sandra. (University of Ottawa (Canada), 1997)
Mainstream psychological research has paid insufficient attention to how women sexually abused in childhood live their intimate adult relationships, and even less to the mutual experience of both partners and the potential for healing within relationship. This empirical-phenomenological study is based upon the written and oral accounts of two couples, who had been in committed relationships for at least five years and where the women had been abused by their fathers in childhood. Following the rigorous and systematic phenomenological method devised by Giorgi (1985), the study explicates and articulates the subjective and intersubjective meaning-structures of how these two couples live relationally with the aftermath of child sexual abuse. The phenomenological analysis resulted in six situated structures for the four individuals and two couples. Further reflection upon these situated structures revealed a matrix of four major interrelated themes common to the experience of both women in our study. These themes were: living a life-world pervaded by embodied vulnerability, insecurity and fear; tenuous-being-in-control and being-all-responsible; embodied suffering; and, existential aloneness--the last three were also found to be dialectically related. These themes were interrelated in a compellingly repetitive pattern which further elaborated the temporal dimension of how the women's abusive pasts continue to re-invade their present existences. Three dialectically related themes emerged for the two men in the study: Caring, feeling-controlled, and putting-aside of self and restriction-of-life-world. When woven together, the themes for the women and the men formed a matrix of dialectically and/or responsively related themes for the couples. Despite serious difficulties, these couples were managing to preserve the resilient structures of their relationships. Our analysis showed that they were struggling toward subjective and intersubjective transformation. Furthermore, the analysis suggested that the theme of transformation was being manifested through the communication of shared understanding, and through seeking mutuality in caring for the being and becoming of both self and other. The unique findings of this phenomenological study fundamentally extend beyond previous understandings of how the aftermath of child sexual abuse is lived in adult intimate relationships.
Keywords: Psychology, Social.